TC Genotype of rs17782313 Near MC4R Gene Increases Obesity Risk - Maharani, Amrina; Puspasari, Anggelia; Maharani, Citra; Enis, Rina Nofri; Aurora, Wahyu Indah Dewi; Halim, Rita (Cell and BioPharmaceutical Institute, 2025)
Background: The genetic variant rs17782313 near the melanocortin-4-receptor gene (MC4R) is one of the robust risk factors for obesity and may be linked to its effect on dietary intake, which has different effect sizes between populations. The association between rs17782313 and obesity and dietary intake has not yet been published with the population from Jambi Malay. This study was conducted to analyze the association of genetic variation of MC4R rs17782313 and dietary intake among the Jambi Malay population.Materials and methods: This study was an unmatched case-control study with 110 subjects, consisting of 55 obese and 55 non-obese individuals. All the subjects were Jambi Malay who reside in Jambi Province and are aged 19-60 years. The MC4R rs17782313 genotype was measured using the tetra amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) method. Dietary data were collected through food recall and analyzed using the NutriSurvey. Bivariate and multivariate analyses were performed.Results: Bivariate analysis showed that subjects with TC genotype increased risk for obesity (p-value: 0.043; OR (95%CI): 3.044 (1.001-9.259). Multivariate analysis adjusted for age, gender and dietary intake, showed similar trends: the TC genotype increased the risk of obesity (p-value: 0.038; OR (95%CI): 3.376 (1.069-10.655). Dietary intake, including total calories, fat, carbohydrate, and protein intake, did not show a statistically significant association with the rs17782313 genotype in obese and non obese groups (p-value>0.05).Conclusion: The TC genotype of rs17782313 near the MC4R gene significantly increases the obesity risk in the Jambi Malay population, independent of dietary intake.Keywords: obesity, MC4R, rs17782313, Malay, Jambi